Contemporary Germany a handbook - Lewis, Derek 1947- (Arnold [u.a.], 2001)
Studying German? Spending a year abroad in Germany? Or maybe going to work there? Then you'll need this handbook to contemporary Germany and the German language. Packed with essential information on politics, the economy and institutions, it covers the basics that are taken for granted by most Germans. Intended for readers without specialist knowledge in any of the subjects covered, this is an invaluable handbook for English-speaking students of German. Each chapter contains a German/English glossary giving guidance on the use of specialist terms in context. Covering German history, politics, the economy, education, the media and the state, the handbook provides a vast amount of information especially geared to student needs.
Includes bibliographical references (p. 290 -299) and index
Keywords: Politik; Wirtschaft; Landeskunde; Allemagne - Civilisation - Guides, manuels, etc; Allemagne - Conditions sociales - 1990- - Guides, manuels, etc; Allemagne - Conditions économiques - 1990- - Guides, manuels, etc; Allemagne - Politique et gouvernement - 1990-1998 - Guides, manuels, etc; Allemagne - Politique et gouvernement - 1998- - Guides, manuels, etc; Deutschland; Germany -- Civilization -- Handbooks, manuals, etc; Germany -- Economic conditions -- 1990- -- Handbooks, manuals, etc; Germany -- Politics and government -- 1990- -- Handbooks, manuals, etc; Germany -- Social conditions -- 1990- -- Handbooks, manuals, etc